For the term of its national life : the Australian (imagi)nation. - Holliday, Brian (Curtin University, 1993)
This thesis is divided into two sections; a theoretical section which looks at the analytic construction of collective identities, and a section which applies the theory to two Australian novels. The first four chapters use the theories of Roy Wagner, Benedict Anderson, Jacques Lacan and Homi Bhabha to look at the often unconscious construction of culture and national, and at the process of hybridity to which those constructions are continually subject.The next three chapters examine Glenda Adamss Games of the Strong and Nicholas Haslucks The Bellarmine Jug showing how an unconscious development of Australian themes runs through the novels, regardless of a lack of Australian characters and setting. The novels show the complex, unique and frequently misunderstood position Australia holds between the cultures, nations and civilisations of the East and the West.The conclusion draws together the principal arguments of the thesis and highlights some concerns which they imply for Australian and its national imagination.